Interacting multiagent systems : kinetic equations and Monte Carlo methods - Pareschi, Lorenzo; Toscani, Giuseppe (Oxford University Press, 2014)
The description of emerging collective phenomena and self-organization in systems composed of large numbers of individuals has gained increasing interest from various research communities in biology, ecology, robotics and control theory, as well as sociology and economics. Applied mathematics is concerned with the construction, analysis and interpretation of mathematical models that can shed light on significant problems of the natural sciences as well as our daily lives. To this set of problems belongs the description of the collective behaviours of complex systems composed by a large enough n.